Soil seed bank compositional change constrains biodiversity in an invaded species-rich woodland - Fisher, J.; Loneragan, W.; Dixon, Kingsley; Veneklaas, E. (Elsevier, 2009)
Relationships between plant invasion and the soil seed bank in highly diverse fire adapted mediterranean woodlands are poorly understood, yet critical for that ecosystem's conservation. Within the biodiversity hotspot of southwest Australia we investigated the composition and diversity of the Banksia woodland soil seed bank in good condition (GC), medium condition (MC) and poor condition invaded by the South African perennial species Ehrharta calycina (PCe) and Pelargonium capitatum (PCp). The investigation assessed three questions: (1) Do soil seed banks of invaded sites have fewer germinants of native species and more germinants of introduced (non-native) species than sites with minimal invasion? (2) Do soil seed banks show shifts in ecological functional types with invasion? (3) Is the soil seed bank of introduced species persistent? Native species germinants, mainly shrubs and perennial herbs, were highest in GC sites and least in poorer condition sites suggesting a reduction in their numbers had occurred over time. Introduced germinants were dominated by perennial and annual grasses, and annual herbs. E. calycina had the greatest seed density (8328 germinants m-2). More introduced than native germinants occurred in the litter. Rapid germination of introduced species (30% in week 1) compared to native species (4% in week 1) provides the capacity for their early dominance. A limited native soil seed bank and dominant persistent introduced soil seed bank represent great challenges for the structural and functional conservation and restoration of woodland ecosystems. This study provides key new knowledge, applicable to a wide range of ecosystems, to help formulate conservation protocols to control dominant introduced species and conserve and restore biodiverse-rich woodlands. © 2008 Elsevier Ltd. All rights reserved.